Family support and quality of life of schizophrenia patients - Ni Made Setiawati; Anak Agung Sagung Sawitri; Cokorda Bagus Jaya Lesmana (International Journal of Public Health Science (IJPHS), 2021)
Schizophrenia remains a global issue. More than half of those living with schizophrenia have yet to receive appropriate treatment that led to the impeded of their recovery and the low quality of life. This study aimed to understand the relationship between familial supports with the quality of life (QOL) of persons with schizophrenia. The cross-sectional study was conducted on randomly selected 161 outpatients at 13 community health centers (puskesmas). Family support and quality of life data were collected by interviewing the respondents with the Friedman’s family support questionnaire and WHO quality of life (WHOQOL-BREF) questionnaire. Subsequently, data was analyzed using logistic regression. The respondents have a mean age of 45 years, mostly males, have completed high school, mostly unemployed and unmarried. Instrumental (AOR=3.177; 95%CI 1.01-9.91) and appraisal support (AOR=7.620; 95%CI 2.83-20.4) were significantly associated with QOL. Conversely, no significant relationship was found between emotional (AOR=1.345; 95%CI 0.46-3.88) and informational (AOR=2.515; 95%CI 0.85-7.42) support toward QOL. Employment, being married and not experiencing relapse were significantly related to QOL. Instrumental support and appraisal support are important factors in determining the quality of life of persons with schizophrenia. Hence, the government needs to expand the roles of family and community to support these roles.